Effects of dietary energy on reproductive function and production in suckled beef cows - Perry, R.C.; Corah, L.R.; Beal, W.E.; Kiracofe, G.H.; Cochran, R.C.; Simms, D.D.; Brethour, J.R.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Twenty-eight Hereford x Angus cows were utilized to determine the effects of dietary energy level before and after calving on reproductive function and production in suckled beef cows. Low levels of dietary energy before calving resulted in losses of body composition prior to calving, reduced calf birth weight, lengthened intervals from calving to ovulation, and decreased milk production and calf weight at 70 d of age (P<.05). Low levels of dietary energy after calving decreased measures of body composition after calving, reduced the percentage of cows that ovulated following calving, and decreased cow milk production and calf weight at 70 d of age (P< .05). We conclude that dietary energy before and after calving impacts the reproductive function and production of suckled beef cows.
Keywords: Beef; Prepartum; Postpartum; Energy; Reproduction; Ultrasound